Study of Process of Migrating the Concept of Business Intelligence from Web Based Computing to Cloud Based Computing (International Journal of Food and Nutritional Sciences, 2021)
Cloud computing is a network of networked systems that offers clients on-demand services. Three distinct service models are used to describe cloud computing: Infrastructure as a Service (IaaS), Software as a Service (SaaS), and Platform as a Service (PaaS). A range of goods and services are offered to customers by various commercial entities. One of these models is available to cloud-based businesses. The model in this article explains how business intelligence assists clients in choosing a specific model for the needed service.